Al-Hadits dalam Pandangan Orientalis (Joseph Schacht) - Muksin, Ucin (Jurnal Ilmu Dakwah, 2008)
Since early period of Islam, opinion about hesitant to position of hadits beÂ  seen. That is ever occurs at classic period of hadits studies, butÂ  stopped with coming Imam Syafiâi. In modern era, the hesitant attitude back occurred by Joseph Schacht, an orientalist. He see a fact about conspiration of specialist of law in Islamic history. With itâs projecting back theory, he investigate un-valid practices by specialist both law and hadits.Since early period of Islam, opinion about hesitant to position of hadits beÂ  seen. That is ever occurs at classic period of hadits studies, butÂ  stopped with coming Imam Syafiâi. In modern era, the hesitant attitude back occurred by Joseph Schacht, an orientalist. He see a fact about conspiration of specialist of law in Islamic history. With itâs projecting back theory, he investigate un-valid practices by specialist both law and hadits.